Financial Literacy Level, Financial Behavior, and Income on Investment Decisions - Ariestiani, Ni Wayan; Putri, I G. A. M. Asri Dwija (E-Jurnal Akuntansi; Vol 35 No 5 (2025)DO - 10.24843/EJA.2025.v35.i05.p10, 2025)
This study aims to determine the effect of financial literacy, financial sophistication, and income on investment decisions. The population in this study were members of the Capital Market Study Group (KSPM) of Udayana University batch 2019 and 2020, which were 116 members. The number of samples in this study were 90 respondents calculated based on the slovin formula. The sampling technique used is simple random sampling technique. The data collection method in this study used a questionnaire. The data analysis technique used was multiple linear regression analysis and used the SPSS program as an analytical tool. The results of this study indicate that financial literacy and financial sophistication have a positive effect on investment decisions, but income has no effect on investment decisions. Keywords: Investment Decisions; Financial Literacy; Financial Sophistication; Income